The E3 Ligase DROUGHT HYPERSENSITIVE Negatively Regulates Cuticular Wax Biosynthesis by Promoting the Degradation of Transcription Factor ROC4 in Rice. Issue 1 (13th December 2017) - Wang, Zhenyu; Tian, Xiaojie; Zhao, Qingzhen; Liu, Zhiqi; Li, Xiufeng; Ren, Yuekun; Tang, Jiaqi; Fang, Jun; Xu, Qijiang; Bu, Qingyun
Abstract : The RING-type E3 ligase DHS cooperates with its putative ubiquitination substrate, the HD-ZIP transcription factor ROC4, to fine-tune wax biosynthesis and the drought stress response in rice. Abstract: Cuticular wax plays crucial roles in protecting plants from environmental stresses, particularly drought stress. Many enzyme-encoding genes and transcription factors involved in wax biosynthesis have been identified, but the underlying posttranslational regulatory mechanisms are poorly understood. Here, we demonstrate that DROUGHT HYPERSENSITIVE ( DHS ), encoding a Really Interesting New Gene (RING)-type protein, is a critical regulator of wax biosynthesis in rice ( Oryza sativa ). The cuticular wax contents were significantly reduced in DHS overexpression plants but increased in dhs mutants compared with the wild type, which resulted in a response opposite that of drought stress. DHS exhibited E3 ubiquitin ligase activity and interacted with the homeodomain-leucine zipper IV protein ROC4. Analysis of ROC4 overexpression plants and roc4 mutants indicated that ROC4 positively regulates cuticular wax biosynthesis and the drought stress response. ROC4 is ubiquitinated in vivo and subjected to ubiquitin/26S proteasome-mediated degradation. ROC4 degradation was promoted by DHS but delayed in dhs mutants. ROC4 acts downstream of DHS, and Os -BDG is a direct downstream target of the DHS-ROC4 cascade. These results suggest a mechanism whereby DHS negatively regulates wax biosynthesis by promoting the degradation of ROC4, and they suggest that DHS and ROC4 are valuable targets for the engineering of drought-tolerant rice cultivars.